Improving the Authoring of Web-based Interactive E-books with FableJS - Silva, Alfredo Tito; de Souza, Welton Marinho; Moraes, Daniel de Sousa; Azevedo, Roberto Gerson; Soares Neto, Carlos de Salles (Anais da Escola Regional de Computação do Ceará, Maranhão e Piauí (ERCEMAPI), 2019)
Electronic books (e-books) first appeared aiming to convert physical books to the digital format. Nevertheless, as technologies advanced, new features were being added to them, creating then, the interactive multimedia e-books. Developing these types of interactive content often requires technical knowledge. However, for authors without this experience, there are few solutions with a high level abstraction paradigm. This article describes FableJS, a library for authoring web applications with nonlinear interactive e-books. Also, a controlled experiment with volunteers using the proposed tool is shown. The study points out that 76.92% of the participants evaluated the library's expressiveness as satisfactory.